ChemInform Abstract: Chiral Phase‐Transfer‐Catalyzed Intramolecular Aza‐Michael Reactions for the Asymmetric Synthesis of Isoindolinones. Issue 30 (July 2015) - Lebrun, Stephane; Sallio, Romain; Dubois, Melanie; Agbossou‐Niedercorn, Francine; Deniau, Eric; Michon, Christophe
Abstract A novel synthetic route to optically active isoindolinones is achieved by asymmetric intramolecular aza‐Michael reaction of ortho‐carbamoyl substituted styryl ketones (I) and (III) in the presence of the oligomeric cinchonium phase‐transfer catalyst (QNC).